PENERAPAN MEDIA PEMBELAJARAN ADOBE FLASH CS6 DALAM MENINGKATKAN HASIL BELAJAR SISWA KELAS X ATPH PADA MATA PELAJARAN ALAT DAN MESIN PERTANIAN DI SMKN 4 JENEPONTO - Mustarin, Amirah; Arifyansah, Rahmat; Rais, Muhammad (Jurnal Pendidikan Teknologi Pertanian, 2019)
This research is a classroom action research, to improve student learning outcomes on the tools and agricultural machinery subject in class X majoring agribusiness food crops and holticulture expertise SMKN 4 Jeneponto with the use of teaching media, Adobe Flash CS6. The subjects of this research were the students of class X agribusiness food crops and holticulture expertise SMK Negeri 4 Jeneponto in the first semester of academic year 2017/2018 that consist of 34 students. This study was conducted in two cycles consisting of four activities, namely: planning, implementation, monitoring/observation and reflection. Data collection and activities of student learning outcomes is done by using a test sheet end of study and observation sheet in the first cycle and the second cycle. The data were analyzed quantitatively and qualitatively. Based on the results of this study concluded that the use of Adobe Flash CS6 can improve the learning outcomes of class X ATPH SMKN 4 Jeneponto. The first cycle test showed learning completeness 52.94% and the second cycle test showed that all students, 34 students, were declared 100% complete.